Writing and publishing process of a multidisciplinary multi-authored research article / Ali Derahvasht - Ali, Derahvasht (2017)
This study aims to explore the writing and publishing process of a multidisciplinary multi-authored research article. Participants of this case study were a team of eight multidisciplinary researchers in chemistry, physics, and engineering in a leading research university in Malaysia. The participants conducted their research project during five months. They produced nine drafts of the article until the final draft was published in an on-line journal. Two theoretical frameworks guided this study. Larsen-Freeman & Cameron (2008) provided the main theoretical lens for seeing the entire process of writing and publishing a research article as a system of interrelated components. Additionally, Grabe & Kaplan’s (1997) model of writing was another framework used for the analysis of text, comprising the nine drafts of the research article. This case study benefited from a naturalistic method of enquiry and qualitative approach in conducting observations, interviews, and collection of documents and other artifacts which provided the sources of data. The multiple authors were interviewed mostly after their laboratory experiments, team discussions, or production of drafts in order to cross check the findings from observations and drafts of the article. The collected data were coded and later categorized and the themes were emergent from the categorized data. In the analysis of findings, the themes were supported by triangulation of data. Findings from the analysis of data revealed that in doing the authentic task of writing and publishing a research article, writing and publishing are not two separate processes, and the end of one is not the beginning of the other. Instead, writing and publishing are two integrated processes, each comprising several sub-processes such as data collection, submission of final drafts to journals, and peer-review of drafts. The findings also unveiled the complexities within the process of writing and publishing multidisciplinary multi-authored research article. Among the findings were issues related to authorship, multiplicity of authors, and multidisciplinary nature of today’s research. Although many scholars have examined authorship, this study revealed that co-authoring a multidisciplinary multi-authored research article depends on many unpredictable aspects and requires adequate precautions and considerations. Interviews showed that segments of the multi-authored text were frequently shaped and re-shaped by the multiple authors of the research article who were from different disciplines. A central theoretical contribution of this study is that the multiplicity of writers (authors) were added to the model of writing which originally looked at single-authored texts. This helped in better understanding of the complexities in shaping and re-shaping the research article text. In addition to awareness-building, pedagogical implications of this study include providing the principles of authorship for novice researchers, and several lessons for conflict management during the process of co-authoring research papers. Another implication involves suggestions of the content of a workshop for staff improvement. Additionally, recommendations for professional practice and future research on writing-for-publication of research articles are provided in the final chapter of this study.